Analytical Solutions for Transport Processes Fluid Mechanics, Heat and Mass Transfer - Brenn, Günter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides analytical solutions to a number of classical problems in transport processes, i.e. in fluid mechanics, heat and mass transfer. Expanding computing power and more efficient numerical methods have increased the importance of computational tools. However, the interpretation of these results is often difficult and the computational results need to be tested against the analytical results, making analytical solutions a valuable commodity. Furthermore, analytical solutions for transport processes provide a much deeper understanding of the physical phenomena involved in a given process than do corresponding numerical solutions. Though this book primarily addresses the needs of researchers and practitioners, it may also be beneficial for graduate students just entering the field. .
Part I Fluid Mechanics -- Part II Heat and Mass Transfer -- Part III Appendix.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Differential equations; Continuum mechanics; Fluid mechanics; Engineering Thermodynamics, Heat and Mass Transfer; Differential Equations; Continuum Mechanics; Engineering Fluid Dynamics